KOMUNIKASI POLITIK DALAM PEMILIHAN KALEBUN DI DESA SANATENGAH KECAMATAN PASEAN KABUPATEN PAMEKASAN - Sudahri Sudahri (Universitas Muhammadiyah Jember, 2018)
Pilkades as a venue for political consolidation at the village level provides an educating political education. Residents are openly confronted with prospective